Vegetacijska podoba vrste Carex rostrata v Sloveniji - Martinčič, Andrej (Hacquetia, 2004)
The authors discuss the vegetational status of the Carex rostrata species in Slovenia, which presents a certain amount of problems also in other parts of Middle Europe. Based on the floristic inventory, the relevés with species Carex rostrata were classified into four different classes. The most frequent are the relevés made on rich minerotrophic hens in the montane zone. Belongingto the class Scheuchzerio-Caricetea fuscae they were classified into the association Caricetum rostrate Osvald 1923 em. Dierssen 1982...
Keywords: fitocenologija; močvirja; nizko barje; phytosociology; Slovenia; Slovenija; šaši (botanika); visoko barje